Polymeric concentrated electrolyte enables simultaneous stabilization of electrode/electrolyte interphases for quasi‐solid‐state lithium metal batteries. Issue 4 (30th January 2023) - Yang, Guanming; Hou, Wangshu; Zhai, Yanfang; Chen, Zongyuan; Liu, Chengyong; Ouyang, Chuying; Liang, Xiao; Paoprasert, Peerasak; Hu, Ning; Song, Shufeng
Abstract: To achieve next‐generation lithium metal batteries (LMBs) with desirable specific energy and reliability, the electrolyte shown simultaneously high reductive stability toward lithium metal anode and oxidative stability toward high‐voltage cathode is of great importance. Here, we report for the first time that high‐concentration lithium bis(fluorosulfonyl)imide (LiFSI) initiates ring‐opening polymerization of 1, 3‐dioxolane in presence of ethylene carbonate and ethylmethyl carbonate to produce in‐situ a novel polymeric concentrated quasi‐solid electrolyte (poly‐CQSE). The unique poly‐CQSE with 10 M LiFSI forms a mixed‐lithiophobic‐conductive LiF‐Li3 N solid electrolyte interphase on lithium metal anode, and a F‐rich conformal cathode electrolyte interphase on LiNi0.5 Co0.2 Mn0.3 O2 (NCM523) cathode simultaneously. As a result, the poly‐CQSE not only enables stable Li plating/stripping of metallic Li anode at a sound Coulombic efficiency of 95.3% without dendrite growth, but also enables a stable cycling of the Li||NCM523 quasi‐solid‐state LMB at a capacity retention of 94% over 100 cycles. Abstract : High‐concentration LiFSI can initiate ring‐opening polymerization of DOL in presence of EC and EMC, forming a new polymeric concentrated quasi‐solid electrolyte, which enables simultaneous stabilization of electrode/electrolyte interphases, leading to a high Coulombic efficiency of 95.3% and excellent cycling performance of 94% capacity retention in Li||NCM523 quasi‐solid‐state lithium metal battery.